Automatisation d’un système de stockage/déstockage d’un magasin par PLC SIEMENS S7-1214 - EL-HOUITI Maria Kheira; CHIKHI Walid; Dr Aboubakeur HADJAISSA (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT D’ELECTRONIQUE, 2022)
The objective of this project is to design an automated system using a PLC, such system capable of controlling and supervising a warehouse, the studied system capable of storing and destocking pieces with considerable speed and has difficult places to reach. The programming of the specifications of this system was made in a PLC of the manufacturer SIEMENS (S7-1200) under the environment TIA Portal, also the different validation tests of this program are made in the same environment. Thus, the development of a Human-Machine interface by the WinCC software that is integrated in the TIA Portal, in order to allow the operator to visualize and analyze the system study.
Option : Automatique et informatique industrielle